ADMS-Urban: developments in modelling dispersion from the city scale to the local scale. (28th December 2012) - Stocker, Jenny; Hood, Christina; Carruthers, David; McHugh, Christine
Many countries perform national air quality assessments using grid-based numerical air dispersion models, generally referred to as 'regional' models. Advantages of these models include the ability to use temporally and spatially varying meteorology and model chemical reactions over large temporal and spatial scales. These models usually perform reasonably well against rural and urban background monitors, but predictions at roadside monitors are underestimated. City-scale air dispersion models have been developed to give high spatial resolution, but are usually restricted to use spatially homogeneous meteorological data and to model simplified chemical reactions over short time scales. Thus, regional and city-scale air dispersion models have complementary strengths and a system where a city-scale model is nested within a regional model allows accurate air dispersion modelling over a range of spatial scales. This paper presents preliminary modelling results from a system where the local model ADMS-Urban is nested within the regional model, CMAQ.